The first complete mitochondrial genome and phylogenetic analysis of the ornate flying snake Chrysopelea ornata (Shaw 1802) Colubridae - D. Dinesh; Soma Roy; Ishani Mitra (Scientific Reports)
Abstract The first complete mitochondrial genome sequencing of ornate flying snake (Chrysopelea ornata_Shaw 1802) was conducted utilizing Next-generation sequencing technologies. The complete mitochondrial genome of flying tree snake is 17,252 bp long with a base composition of A-36%, T-27%, G-12%, C-25% with a GC content of 38%. Chrysopelea ornata also shows mitogenome organization of 37 genes including 13 protein-coding genes, 22 tRNA genes, two rRNA genes and two non-coding regions. Nine genes including eight tRNAs and NAD6 were encoded. Phylogenetic investigations, utilizing the entire mitochondrial genome of chrysopelea ornata, reveal the strongest association with the genus Ptyas.